2015
DOI: 10.1007/s00170-015-7377-7
|View full text |Cite
|
Sign up to set email alerts
|

New schemes of forging plates, shafts, and discs

Abstract: This paper presents the various ways of forging large forged pieces such as shafts, plates, and discs. A finite element method was used to simulate open die forging processes such as forging by flat dies with a slant, forging by staged dies, and upsetting of profiled workpiece. The parameters of the stress strain state of the billet in these processes were determined, along with the rational parameters for forging plates by flat dies with slant such as tool size and mechanical modes. The optimal die step dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In the experimental tests, a flare at the flange equator arises with a flange diameter of d max =48 mm for a value of r/d 0 =0.25 (r=4.26 mm). The results of the calculations coincide satisfactorily with the results obtained in [1][2][3][4]23].…”
Section: Tablesupporting
confidence: 86%
See 1 more Smart Citation
“…In the experimental tests, a flare at the flange equator arises with a flange diameter of d max =48 mm for a value of r/d 0 =0.25 (r=4.26 mm). The results of the calculations coincide satisfactorily with the results obtained in [1][2][3][4]23].…”
Section: Tablesupporting
confidence: 86%
“…Workpieces of the desired accuracy in shape and size can be obtained in one transition or, due to the plasticity resource depletion, in several transitions associated with intermediate annealing to restore the plasticity of the workpiece material. In the second case, non-monotonic processes of plastic shaping can be used with high efficiency, which is also connected with the formulation and solution of new problems in the theory of plasticity [1][2][3][4].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…A finite element method (FEM) (Zhbankov and Perig 2013a, b; Zhbankov et al 2014, 2016; Perig et al 2013a, b, 2015) in Deform 3D software was used in the simulation of the upsetting process. The diameter of the billet is 18 mm, the length is 20 mm, and the material is carbon steel with 0.70% C. The initial temperature of the billet is 1100 °C and the initial temperature of the tools is 20 °C.…”
Section: Phenomenological Numerical Approachmentioning
confidence: 99%
“…Research into the dynamics of forging the axial looseness is reported in paper [16]. Designing the new technological forging processes when making forgings with special purposes requires information on the dynamics of forging the axial defects in an ingot at deformation according to new schemes.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%